Integrative Insights into Cardiac Health from Ayurveda (International Journal of Ayurveda and Pharma Research, 2025)
Cardiovascular diseases are increasingly prevalent in the era of globalization, and following the COVID-19 pandemic, sudden fatal cardiac events are being reported more frequently. Ayurveda is not merely a system for the treatment of diseases; it also provides comprehensive guidelines for leading a healthy life, both physically and mentally. Ayurvedic texts describe Dincharyā (daily regimen), Ritucharyā (seasonal regimen), and Āhāra (dietary regimen) that nourishes the body as essential measures for maintaining health and preventing disease. Ayurveda also offers a wide range of therapeutic interventions for Hṛdroga (cardiac disorders), which play a crucial role in promoting longevity and exert cardioprotective effects. Among these, Arjuna (Terminalia arjuna) is well recognized for its cardioprotective properties and is widely used across the world for the management of various cardiac conditions. The Ayurvedic approach to the treatment of Hṛdroga includes Nidāna Parivarjana (avoidance of known causative factors), administration of herbal and Herbo-mineral formulations, and Pañchakarma therapies, which contribute significantly to disease management. Importantly, Ayurveda emphasizes addressing the root cause of disease, thereby offering not only curative but also preventive strategies, which are crucial in the context of cardiovascular health. In recent years, cardiovascular disorders have been increasingly observed among the younger population, who represent the future of the nation. Therefore, emphasis must be placed on an integrated approach to the prevention and management of cardiac diseases. There is an urgent need to adopt integrative strategies that combine Ayurvedic principles with modern medical approaches, particularly for individuals at high risk. The use of Ayurvedic cardioprotective agents as a first-line defence may play a pivotal role in safeguarding the vital organ the heart.